2015
DOI: 10.1105/tpc.15.00234
|View full text |Cite
|
Sign up to set email alerts
|

HIGH CHLOROPHYLL FLUORESCENCE145 Binds to and Stabilizes the psaA 5′ UTR via a Newly Defined Repeat Motif in Embryophyta

Abstract: ORCID IDs: 0000-0003-2740-5991 (N.M.); 0000-0003-2973-9514 (J.M.)The seedling-lethal Arabidopsis thaliana high chlorophyll fluorescence145 (hcf145) mutation leads to reduced stability of the plastid tricistronic psaA-psaB-rps14 mRNA and photosystem I (PSI) deficiency. Here, we genetically mapped the HCF145 gene, which encodes a plant-specific, chloroplast-localized, modular protein containing two homologous domains related to the polyketide cyclase family comprising 37 annotated Arabidopsis proteins of unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…In addition, subchloroplast fractionation and subsequent immunoblot analysis showed that NFU1 and NFU2 are located in the chloroplast stroma (Yabe et al, 2004). The three plastidtargeted NFU proteins contain an N-terminal redoxactive NFU domain with the conserved CXXC motif and a C-terminal redox-inactive NFU domain; the two mitochondrion-targeted NFU proteins contain an N-terminal domain that is unique to nonplastid types of eukaryotic NFU proteins and a C-terminal redoxactive NFU domain with the conserved CXXC motif (Gao et al, 2013;Manavski et al, 2015). Immunoblot analysis showed that the three plastid-targeted NFU proteins exhibited different expression patterns: NFU1 is expressed at a very low level; NFU2 is expressed ubiquitously in all the tissues tested, including roots, true rosette leaves, cauline leaves, flower stalks, and flowers; and NFU3 is expressed predominantly in the aerial portion of the plants (Yabe et al, 2004).…”
mentioning
confidence: 99%
“…In addition, subchloroplast fractionation and subsequent immunoblot analysis showed that NFU1 and NFU2 are located in the chloroplast stroma (Yabe et al, 2004). The three plastidtargeted NFU proteins contain an N-terminal redoxactive NFU domain with the conserved CXXC motif and a C-terminal redox-inactive NFU domain; the two mitochondrion-targeted NFU proteins contain an N-terminal domain that is unique to nonplastid types of eukaryotic NFU proteins and a C-terminal redoxactive NFU domain with the conserved CXXC motif (Gao et al, 2013;Manavski et al, 2015). Immunoblot analysis showed that the three plastid-targeted NFU proteins exhibited different expression patterns: NFU1 is expressed at a very low level; NFU2 is expressed ubiquitously in all the tissues tested, including roots, true rosette leaves, cauline leaves, flower stalks, and flowers; and NFU3 is expressed predominantly in the aerial portion of the plants (Yabe et al, 2004).…”
mentioning
confidence: 99%
“…Our first reason was the lack of complementation experiments and RNA-binding studies as well as enzymatic tests of DPT1. Second, with HCF145, a factor required for psaA/psaB/rps14 RNA accumulation had already been unambiguously identified (Manavski et al, 2015). Indeed, genotyping experiments in two different laboratories (Jörg Meurer and Torsten Möhlmann) failed to confirm the described T-DNA insertion into the At3g18680 (N829192) locus.…”
Section: Lack and Reduction Of Pumpkin Does Not Cause A Typical Psi Pmentioning
confidence: 99%
“…RNA-gel-blot analyses, total RNA isolation, electrophoresis, blotting, and hybridization with radioactive labeled probes were carried out as described by Manavski et al (2015). Oligonucleotides and primers for PCR-probes are listed in Supplemental Table S1.…”
Section: Rna-gel-blot Hybridization Rt-pcr and Ppementioning
confidence: 99%
See 1 more Smart Citation
“…Following its application for screening of Chlamydomonas mutant libraries (see for example Harris, 1989 ) the concept was tested in higher plants ( Miles and Daniel, 1973 ) and employed for the screening of maize ( Miles and Daniel, 1974 ; Barkan et al, 1986 ; Taylor et al, 1987 ) and Arabidopsis mutant libraries ( Dinkins et al, 1994 ; Meurer et al, 1996b ). Several factors involved in chloroplast biogenesis were identified using the hcf phenotyping method, including the maize proteins HCF106, HCF60, and HCF136 (reviewed in: Belcher et al, 2015 ) and the Arabidopsis proteins HCF5 ( Dinkins et al, 1997 ), HCF101 ( Lezhneva et al, 2004 ), HCF107 ( Felder et al, 2001 ), HCF109 ( Meurer et al, 1996a ), HCF145 ( Lezhneva and Meurer, 2004 ; Manavski et al, 2015 ), HCF152 ( Meierhoff et al, 2003 ) and LPA1 ( Peng et al, 2006 ).…”
Section: Chl Fluorescence Video Imaging In Forward Genetic Approachesmentioning
confidence: 99%